Family-Centered Care Improves Clinical Outcomes of Very-Low-Birth-Weight Infants: A Quasi-Experimental Study - Bo Lv; Xi-ronga Gao; Jing Sun; Tao-tao Li; Zhen-ye Liu; Li-hui Zhu; Jos M. Latour; Jos M. Latour (Frontiers Media S.A., 2019)
Background: Survival of very-low-birth-weight infants is improving in neonatology and family-centered-care might contribute to premature infants' clinical outcomes.Aim: To evaluate a family-centered care intervention on clinical outcomes of very-low-birth-weight infants.Methods: A quasi-experimental study was conducted in a Chinese NICU between June 2016 and June 2017. The intervention included parental education of basic care knowledge and skills followed by active participation in care for at least 4 h a day. A total of 319 very-low-birth-weight infants were recruited by convenience sampling; intervention group n = 156 and control group n = 163. Primary outcome measures were weight at discharge, length-of-stay, breastfeeding, nasal feeding, total parental nutrition, re-admission, hospital expenses. Secondary outcome measures were infant complications.Results: Infants' weight at discharge was higher in the interventions group (2,654 g vs. 2,325 g, p < 0.001). Nutritional outcomes improved significantly: breastfeeding rate 139 vs. 91, p < 0.001; days of total parental nutrition 25 d vs. 32 d, p < 0.001; gastric feeding days 23 d vs. 35 d, p < 0.001. Length-of-stay and hospital expenses did not differ between both groups. Improved infants' complications were bronchopulmonary dysplasia (32 vs. 51, p = 0.031), retinopathy of prematurity (between groups no/mild and moderate/severe, p = 0.003), necrotizing enterocolitis (6 vs. 18, p = 0.019), and re-admission rate (21 vs. 38, p = 0.023). No differences were observed in intraventricular hemorrhage and nosocomial infections.Conclusion: Very-low-birth-weight premature infants might experience improved clinical health outcomes when parents are present and caring from them. Family-centered care is as a beneficial care model for premature infants and should be recognized and implemented by NICUs where parents have currently limited access.